Thermal analysis of N-carbamoyl benzotriazole derivatives - Kos Ivan; Weitner Tin; Grgac Sandra Flinčec; Jablan Jasna (Acta Pharmaceutica)
Thermal properties of N-carbamoyl benzotriazole derivatives and N,N’,N’’-tribenzyloxyisocyanuric acid were investigated using thermogravimetric analysis and differential scanning calorimetry. The results revealed a difference between structural analogs of N-carbamoyl benzotriazole derivatives. They seem to be in agreement with the previously proposed formation of N,N’,N’’-tribenzyloxyisocyanuric acid from 1-(N-benzyloxycarbamoyl) benzotriazole, via an intermediary N-benzyloxyisocyanate acid, during heating. Substantially different thermal properties were observed for structural analogues, 1-(N-methoxycarbamoyl) benzotriazole and 1-(N-ethoxycarbamoyl) benzotriazole. In contrast to N-benzyloxyisocyanate, no corresponding reactions were observed for their decomposition products, i.e., methoxyisocyanate and ethoxyisocyanate.